EFFECT OF COMPANY SIZE, LEVERAGE, RETURN ON INVESTMENT, EARNINGS PER SHARE AND RETURN ON ASSETS TO RETURN RECEIVED by SHAREHOLDERS - Tania Tamba; Yogina Saskia Sinaga; Yenni Tampubolon; Siti Dini; Ratna Sari Dewi (Jurnal Ipteks Terapan, 2023)
This study aims to examine the effect of firm size , leverage, return On investment, earning Per share, return On Assets against return Which accepted holder shares (Empirical Study on the Food and Beverage Industry on the Indonesia Stock Exchange). Every data Which needed official data from report finance annual Which originate from IDX. Population applied in this study, namely Food and Beverage companies registered at Indonesia Stock Exchange for the 2019-2021 period. Of the 29 companies listed on the Stock Exchange In Indonesia, there are only 24 companies used as samples in this study. Sample the chosen with use method purposive Sampling . For analyze data, study This use regression double linear And done test hypothesis with test t (Partial) And test F (Simultaneously) in level significance 0.05. Results from study This that is : (1) Variable Size Company, return On Assets (ROA) influential positive to return stock . (2) Variable leverage, return On Investments (ROI) influential negative to return stock . (3) Variable earning Per Share No influential to stock returns . (4) Influence Company Size , Leverage, Return On Investment, earning Per Share and return On Assets in a manner simultaneous influential to return stock